An American abroad [videorecording (DVD)] - Kimpton, Maricia; Kimpton, Maricia; McAleece, Justin; McAleece, Justin; Gross, Brian; Gross, Brian; King, Jacy (Freestyle Digital Media, 2025)
Visit Greece, Africa, and Amsterdam in this hilarious rom-com about a free spirited travel host and her uptight boyfriend's wild love story. Marcia's lust for adventure has Arnold on a walking safari, swimming with sharks and wine tasting in France.